Influence of different adhesion strategies on glass fiber post retention - Nadler, Ana-Michelle-Oliveira; da Silva, Evair-Josino; Lins-Filho, Paulo-Cardoso; Dias, Marlon-Ferreira [UNESP]; Guimarães, Renata-Pedrosa; da Silva, Claudio-Heliomar-Vicente; Silva, Sérgio-dos Santos; Gomes, Anderson-Stevens-Leonidas (Medicina Oral, S.L., 2023)
Background: Failures in glass fiber post (GFP) retention may be associated with low adhesion achieved in root dentin. Material and Methods: 55 single-rooted premolars were endodontically treated and distributed according to different adhesion strategies (n=11): G1: RelyX ARC (3M ESPE; etch-rinse strategy); G2: Relyx Ultimate (3M ESPE; etch-rinse strategy); G3: AllCem (FGM; etch-rinse strategy); G4: Relyx Ultimate (3M ESPE; self-etching strategy); G5: RelyX U200 (3M ESPE; self-adhesive strategy). For Bonding Strength (BS) analysis, the roots were sectioned in slices (1.0mm thickness) corresponding to each root third and submitted to push-out test. The type of failure was assessed by scanning electron microscopy (SEM). Results: The highest BS averages were found in G2 and G3. However, in the middle and apical root thirds, G3 showed statistically similar results to G4 and G5. In the cervical and middle third, G1 was statistically similar to G4 and G5. The mixed type of failure was the most common in all groups. Conclusions: self-etching (G4) and self-adhesive resin (G5) cements, showed similar BS results of immediate bonding in the cementation of GFP compared to conventional resin cements (G1, G2, G3).
Keywords: Dental Bonding; Dental Cements; Dentin-Bonding Agents; Post and Core Technique